Genetic mapping of natural variation in a shade avoidance response : ELF3 is the candidate gene for a QTL in hypocotyl growth regulation - Coluccio, M. Paula (2011)
Fil: Coluccio, M. Paula. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura (IFEVA). Buenos Aires, Argentina.